The Effect of Environmental Factors on the Nutrition of European Beech (Fagus sylvatica L.) Varies with Defoliation - Ognjenović, Mladen; Seletković, Ivan; Marušić, Mia; Jonard, Mathieu; Rautio, Pasi; Timmermann, Volkmar; Tadić, Melita Perčec; Lanšćak, Miran; Ugarković, Damir; Potočić, Nenad (MDPI AG, 2022)
Despite being adapted to a wide range of environmental conditions, the vitality of European beech is expected to be significantly affected by the projected effects of climate change, which we attempted to assess with foliar nutrition and crown defoliation, as two different, yet interlinked vitality indicators. Based on 28 beech plots of the ICP Forests Level I network, we set out to investigate the nutritional status of beech in Croatia, the relation of its defoliation and nutrient status, and the effects of environmental factors on this relation. The results indicate a generally satisfactory nutrition of common beech in Croatia. Links between defoliation and nutrition of beech are not very direct or very prominent; differences were observed only in some years and on limited number of plots. However, the applied multinomial logistic regression models show that environmental factors affect the relationship between defoliation and nutrition, as climate and altitude influence the occurrence of differences in foliar nutrition between defoliation categories.
Keywords: tree vitality; foliar composition; stoichiometry; climate change; ICP Forests